Dominasi Tanda Identitas dalam Foto Esai Sepak Bola di Museum Olahraga - Dedy Setiawan; Tisna Prabasmoro; Widyo Nugrahanto (Publikasi Indonesia, 2022)
The National Sports Museum was formed and intended for the public to learn about sports development in Indonesia. This research has the objectives, namely; to explain what the national football identity signs are in the football essay photo at the national sports museum and what football identity is dominantly present in the photo essay, and the meaning of its appearance. This study uses Roland Barthes' semiotics method to analyze the identity of the signs and meanings contained in football essay photos at the national sports museum. The dominant national football identity presented by the museum is football as a recreational sport and as a professional sport slightly raised due to the unstable development of Indonesian football achievements and tends to decline.